Fifty Years of Technological Innovation: Potential and Limitations of Current Technologies in Abdominal Magnetic Resonance Imaging and Computed Tomography. Issue 9 (September 2015) - Attenberger, Ulrike I.; Morelli, John; Budjan, Johannes; Henzler, Thomas; Sourbron, Steven; Bock, Michael; Riffel, Philipp; Hernando, Diego; Ong, Melissa M.; Schoenberg, Stefan O.
Abstract : Abstract: Magnetic resonance imaging (MRI) has become an important modality for the diagnosis of intra-abdominal pathology. Hardware and pulse sequence developments have made it possible to derive not only morphologic but also functional information related to organ perfusion (dynamic contrast-enhanced MRI), oxygen saturation (blood oxygen level dependent), tissue cellularity (diffusion-weighted imaging), and tissue composition (spectroscopy). These techniques enable a more specific assessment of pathologic lesions and organ functionality. Magnetic resonance imaging has thus transitioned from a purely morphologic examination to a modality from which image-based disease biomarkers can be derived. This fits well with several emerging trends in radiology, such as the need to accurately assess response to costly treatment strategies and the need to improve lesion characterization to potentially avoid biopsy. Meanwhile, the cost-effectiveness, availability, and robustness of computed tomography (CT) ensure its place as the current workhorse for clinical imaging. Although the lower soft tissue contrast of CT relative to MRI is a long-standing limitation, other disadvantages such as ionizing radiation exposure have become a matter of public concern. Nevertheless, recent technical developments such as dual-energy CT or dynamic volume perfusion CT also provide more functional imaging beyond morphology. The aim of this article was to review and discuss the most important recent technical developments in abdominal MRI and state-of-the-art CT, with an eye toward the future, providing examples of their clinical utility for the evaluation of hepatic and renal pathologies.